Nonredox trivalent nickel catalyzing nucleophilic electrooxidation of organics - Yan, Yuandong; Wang, Ruyi; Zheng, Qian; Zhong, Jiaying; Hao, Weichang; Yan, Shicheng; Zou, Zhigang (Nature communications, 2023)
A thorough comprehension of the mechanism behind organic electrooxidation is crucial for the development of efficient energy conversion technology. Here, we find that trivalent nickel is capable of oxidizing organics through a nucleophilic attack and electron transfer via a nonredox process. This nonredox trivalent nickel exhibits exceptional kinetic efficiency in oxidizing organics that possess the highest occupied molecular orbital energy levels ranging from −7.4 to −6 eV (vs. Vacuum level) and the dual local softness values of nucleophilic atoms in nucleophilic functional groups, such as hydroxyls (methanol, ethanol, benzyl alcohol), carbonyls (formamide, urea, formaldehyde, glucose, and N-acetyl glucosamine), and aminos (benzylamine), ranging from −0.65 to −0.15. The rapid electrooxidation kinetics can be attributed to the isoenergetic channels created by the nucleophilic attack and the nonredox electron transfer via the unoccupied e g orbitals of trivalent nickel (t 2g 6 e g 1 ). Our findings are valuable in identifying kinetically fast organic electrooxidation on nonredox catalysts for efficient energy conversions. A good understanding of the mechanism behind organic electrooxidation is crucial for the development of efficient energy conversion technology. Here, the authors find that trivalent nickel is capable of oxidizing organics through a nucleophilic attack and electron transfer via a non-redox process.